Ancestral deceit and labile evolution of nectar production in the African orchid genus Disa - Johnson, Steven D.; Hobbhahn, Nina; Bytebier, Benny (Biology letters (2005), 2013)
An outstanding feature of the orchid family is that approximately 30–40% of the species have non-rewarding flowers and deploy various modes of deception to attract pollinators, whereas the remaining species engage in pollination mutualisms based on provision of floral rewards. Here, we explore the direction, frequency and reversibility of transitions between deceptive and rewarding pollination systems in the radiation of the large African genus Disa, and test whether these transitions had consequences for diversification. By optimizing nectar production data for 111 species on a well-resolved phylogeny, we confirmed that floral deception was the ancestral condition and that nectar production evolved at least nine times and was lost at least once. Transitions to nectar production first occurred ca 17 million years ago but did not significantly affect either speciation or extinction rates. Nectar evolved independently of a spur, which was lost and gained multiple times. These results show that nectar production can be a highly labile trait and highlight the need for further studies of the genetic architecture of nectar production and the selective factors underlying transitions between deception and mutualism.